Kebijakan Komunikasi di Indonesia: Gambaran Implementasi UU No. 14 tahun 2008 tentang Keterbukaan Informasi Publik - Agusly Irawan Aritonang (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2011)
Freedom of getting information is also one of democracy state’s features since it is expected to stimulate participation of citizen. Furthermore, if there is more public information which can be got freely, it will strengthen the tendency of the change of society type into informative society. Indonesia tried to facilitate its citizens by providing such a basic bill in order to access public information. As a communication policy, this regulation has been implemented since its validity 2 years ago. This implementation of policy such as Bill No. 14 of 2008 talks about Transparency of Public Information become such a complicated problem. Problem related to regulation’s article which has to be as operational as possible when it will be implemented and also about its accuracy are factors that become a success key for public policy implementation involved the communication policy.